Changements de l’occupation des Terres dans la Forêt Classée des Monts Kouffé et sa Périphérie Sud au Bénin (1986-2006) - Mouhamadou, Inoussa Toko (European Scientific Journal, ESJ, 2019)
Monts Kouffe forest reserve and its southern surrounding undergo pressures of fast population growth, shifting cultivation, over pasture, poaching, unfair forestry utilization. This study aims to analyse Monts Kouffe forest reserve and its southern surrounding land use/land cover, to understand their spatiotemporal dynamics. The methodology approach is based on Remote Sensing using 1986 Landsat TM and 2006 Landsat ETM+ satellite data . Cartography was used to produce 1986 and 2006 land use/land cover maps. Geographical Information System using spatial analysis allowed to identify three major changes which are, dry dense forest islands’ fragmentation and their areas’ reduction, Monts Kouffe forest reserve’s savanisation and, agricultural areas’ increasing. Computed land use/land cover areas and the rates of spatial expansion annual mean between 1986-2006 present a major increasing of savannah planted (3%), fields and fallows (4,61%) ares. While the areas of dry dense forest (-1%), light forest (-1,13%), bushland (- 0,35%) and others units (bare soil and burned area) (-7,14%) were reduced. Computed conversion rates are higher for others units (bare soil and burned area) with 99,84%, fields and fallows (90,08%),. But these rates are wheek for dry dense forest (48,56%). So, for biodiversity sustainable conservation this protected area need to be strongly monitored. La forêt classée des Monts Kouffé et sa périphérie sud subissent les pressions de la croissance démographique galopante, de l’agriculture itinérante sur brûlis, du surpâturage, du braconnage et de l’exploitation forestière anarchique. Cette vise à analyser l’occupation des terres en vue de comprendre leur dynamique spatio-temporelle. La méthodologie adoptée est basée sur la Télédétection avec des images satellitaires Landsat TM de 1986 et ETM+ de 2006. La Cartographie pour la réalisation des cartes d’occupation du sol de 1986 et 2006. Les analyses spatiales du Système d’Information Géographique ont permis d’observer, trois changements majeurs, la fragmentation et la réduction des superficies des îlots de forêt dense sèches, la savanisation de la forêt classée des Monts Kouffé et la progression des surfaces agricoles. Les superficies et taux moyens annuels d’expansion spatiale des unités d’occupation desterres calculées entre 1986-2006 montrent une augmentation majeure des superficies de la savane arborée (3%) et des champs et jachères (4,61%). Tandis que celles de la forêt dense sèche (-1%), la forêt claire (-1,13%), la savane arbustive (- 0,35%) et les autres unités dont les sols nus et les zones brûlées (-7,14%) ont diminuées. Les taux de conversion calculés sont plus élevés dans les autres unités (sols nus, zones brûlées) avec 99,84% et les champs et jachères (90,08%). Mais ces taux sont faibles pour les forêts denses sèches (48,56%). Sur ce, pour une conservation durable de la biodiversité cette aire protégée mérite d’être surveillée de près.